DETERMINAN KEPUASAN KONSUMEN PADA RAHMA KEDAI DAN RESTO TAWANGMANGU - Djong, Alexander Mario Retto; Sapeibu, Riza Maria (JURNAL LENTERA BISNIS, 2026)
A quantitative approach was used in this study to examine how service quality, food quality, location, and product price impact consumer satisfaction at Rahma Kedai and Resto Tawangmangu. Samples were taken based on specific criteria (purposive sampling). The Hair formula is used to obtain a sample size of 200 respondents. Data collection was carried out by distributing questionnaires to customers of Rahma Kedai and Resto Tawangmangu. The data was processed using SPSS Version 22 and Microsoft Excel. The data analysis methods used were Instrument Test, Classical Assumptions, and Hypothesis Testing. The statistical results indicate that service quality, food quality, location, and product price can positively and significantly influence consumer satisfaction, both partially and simultaneously. The independent variable has a strong impact on the dependent variable, as indicated by a determination coefficient value of 85.6%. Based on these findings, it is recommended that the owners of Rahma Kedai and Resto Tawangmangu continue to improve food and service quality, optimize the strategic location factor, and set competitive prices to maintain their competitive edge in the restaurant industry.